Pengaruh Kompetensi Kerja, Pengawasan, dan Kepemimpinan terhadap Kinerja Pegawai Bagian Umum dan Perlengkapan Setda Kota Manado - Jacobs, Adriel Philip Kambea; Rantung, Ventje V (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract: The efforts to improve the performance of employee must still receive the most attention from the leadership in carrying out activities in accordance duties and functions effectively and efficiently in order to achieve service excellence. The low performance of employees for this to be one important factor driving the crisis of public confidence in government. Without ignoring the importance of other factors, competence factors of work, supervision and leadership are considered to have a significant effect on the level of employee performance. This study aims to determine and analyze the effect of job competence, supervision and leadership to employee performance. The research was conducted in the city of Manado on the general and equipment division of the regional secretariat Manado city that lasted for 3 months with the study sample numbered 52 people. The method used is survey method with quantitative approach. Techniques of data analysis used a statistical analysis by using multiple regression test. Methods of data collection by observation, interviews and questionnaires. Results of analysis of the data showed a variable coefficient of 0.203 means that job competence when working up a unit of competency, assuming other variables remain the performance of employees has increased by 0.203; supervision variable coefficient of 0.283 means if supervision up a surveillance unit, assuming other variables remain the performance of employees have increase of 0.283, whereas the leadeship variable coefficient of 0.395 means if the leadership up one unit, assuming other variables remain the performance of employees increased by 0.395. The third test of independent variables through multiple regression analysis with the F test indicates that jointly job competency factors, supervision and leadership had different affect on the the performance of employees. Based on the results of the study, this suggests that the increased work competence is supported by supervision and leadership so that the performance becomes better.Keywords : job competence, supervision, leadership, performance